THE USE OF TED TALK VIDEOS TO IMPROVE ESL SPEAKING SKILLS OF BHUTANESE SIXTH-GRADERS - Lhamo, Tshewang; Chalermnirundorn, Nipaporn (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This quasi-experimental study investigated whether the use of TED Talk videos (TTV) improved the speaking skills of 30 Bhutanese ESL learners, and further explored their perceptions towards the use of TTV. A simple random sampling technique was applied to select a section of 30 sixth-graders from a total of three sections. The selected group was treated with TTV as the learning material to improve their English-speaking skills. The quantitative and qualitative data were collected through pretest, posttest, survey questionnaire and focus group interview. The quantitative data were analyzed and interpreted using inferential statistics t-test with p≤.05 level of significance, mean, and standard deviation. Similarly, qualitative data collected through a focus group interview was analyzed employing a thematic analysis. The results revealed a mean of 10.82 for pretest, 15.32 for the posttest, with a mean difference of 4.5. and the significant value (p) obtained was .01. The result indicated higher scores in the posttest, vis-a-vis the pretest of all 30 research participants. The findings from the survey questionnaire and focus group interview also revealed positive perceptions towards the use of TTVs in English-speaking lessons by all participants. Thus, the findings provide an alternative to ESL teachers in Bhutan to teach speaking skills.